Social Entrepreneurship Education for Orphans Through Chicken Farming : A Case Study from Yogyakarta - Yudan Hermawan; A. Hasdiansyah; R.B. Suharta; Riko Septiantoko; Rita Bekti Utami (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to explore in depth the social entrepreneurship education activities of Omah Pak Cilik, the Gerakan Kebaikan community in livestock-based entrepreneurial activities for orphans, including constructing the meaning and reality behind the emergence of these programs and collaboration. The research method used was phenomenological with a qualitative approach. For collecting the data, this research used interviews, direct observation, and directed dialogue with the founder of Omah Pak Cilik, the Actor for the Good Movement, and Orphans. The validity of the research data was obtained through triangulation and then analyzed using the Interpretative Phenomenological Analysis (IPA) approach. This study found that 1) Omah Pak Cilik cooperated with the kindness movement community to organize a KUB Chicken Farm business to solve economic problems, starting with providing understanding related to entrepreneurship to orphans so that an entrepreneurial spirit grows, 2) Orphans were given education and training related to business management and sales skills. 3) The result changed the mindset of orphans for entrepreneurship, improving the economy, and establishing partnerships.